2011
DOI: 10.1186/1471-2180-11-206
|View full text |Cite
|
Sign up to set email alerts
|

Clonal diversity of the glutamate dehydrogenase gene in Giardia duodenalisfrom Thai Isolates: evidence of genetic exchange or Mixed Infections?

Abstract: BackgroundThe glutamate dehydrogenase gene (gdh) is one of the most popular and useful genetic markers for the genotypic analysis of Giardia duodenalis (syn. G. lamblia, G. intestinalis), the protozoan that widely causes enteric disease in humans. To determine the distribution of genotypes of G. duodenalis in Thai populations and to investigate the extent of sequence variation at this locus, 42 fecal samples were collected from 3 regions of Thailand i.e., Central, Northern, and Eastern regions. All specimens w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
1
17
0
1
Order By: Relevance
“…Despite the fact that Giardia is believed to be a strictly clonal (asexual) organism, there is evidence for recombination at the telomeres (but not the internal regions) of some of the chromosomes of the parasite [9,56]. Additional evidence of genetic recombination has been demonstrated at the cellular level in cultured assemblage B trophozoites and in cysts from clinical samples [57], and at the population level within sub-assemblages BIII and BIV [58]. Taken together, these findings may explain the occurrence of discordant genotypes BIII/BIV, as those described in the present survey.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that Giardia is believed to be a strictly clonal (asexual) organism, there is evidence for recombination at the telomeres (but not the internal regions) of some of the chromosomes of the parasite [9,56]. Additional evidence of genetic recombination has been demonstrated at the cellular level in cultured assemblage B trophozoites and in cysts from clinical samples [57], and at the population level within sub-assemblages BIII and BIV [58]. Taken together, these findings may explain the occurrence of discordant genotypes BIII/BIV, as those described in the present survey.…”
Section: Discussionmentioning
confidence: 99%
“…duodenalis in the cyst stage) leading to gene conversion or crossing-over events can most likely achieve this effect [ 52 ], raising the question of whether Giardia is also capable of sexual reproduction. Indeed, evidence of genetic recombination has been demonstrated at the cellular level in cultured assemblage B trophozoites and in cysts from clinical samples [ 53 ], and at the population level within sub-assemblages BIII and BIV [ 47 ]. However, somewhat conflicting results are currently available regarding the potential exchange of genetic material between genotypes of different G .…”
Section: Discussionmentioning
confidence: 99%
“…0.00235 vs. 0.00340 for assemblage A and 0.00433 vs. 0.00620 for assemblage B. Another study from Thailand based on gdh gene [ 24 ] also showed significant higher nucleotide divergence (K) in assemblage B than assemblage A. In the context of the overall worldwide comparison, assemblage B yielded the highest level of genetic diversity followed by assemblage E and assemblage A.…”
Section: Discussionmentioning
confidence: 99%
“…Populations that have been stable over time are expected to have a bimodal and multimodal mismatch distribution [ 37 – 39 ]. However, the influence of selection could be locus-dependent as test for neutrality from other studies suggested that the bg gene was possibly influenced by ongoing purifying selection [ 23 ] while the gdh gene was under neutral selection [ 24 ]. On the other hand, if Giardia undergoes reproduction asexually as it is generally assumed, the population would be made up of independently evolving lineages and mutations are expected to confine to the lineage in which they began [ 11 ], thereby the different rate of mutation with selection pressure might contribute to the excess polymorphism sites but low frequency of haplotype and limit its potential of evolution.…”
Section: Discussionmentioning
confidence: 99%